Low energy consumption and mechanism study of redox flow desalination - Chen, Fuming; Wang, Jian; Feng, Chunhua; Ma, Jinxing; David Waite, T. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Less than 150 ppm water product can be obtained by one-time-continuous charge process in batch mode.•The removal efficiency is up to 95.5% for single-continuous batch-mode treatment.•An unlimited salt removal capacity was demonstrated.•A relatively low average energy consumption down to 8.34 kJ mole−1 salt removed is achievable.•No electrode regeneration is required to realize the full continuous desalination. Low-energy desalination technologies capable of continuous throughput at reasonable operating and maintenance cost are now critically needed. Herein, we present a continuous desalination process with average energy consumption as low as 2.14 kJ mole−1 salt removed achievable when using a 10 mM/10 mM ferri-/ferrocyanide solution that flows continuously between anode and cathode chambers. The salt feed at ~3000 ppm can be continuously desalted to a potable level of less than 150 ppm during the desalination process. At the anode, ferrocyanide is oxidized with electrons released to the external circuit and cations captured to achieve charge balance. Ferricyanide is reduced at the cathode, resulting in the constant transfer of anions from the dilute stream to the concentrate stream. The recycling of the redox mediators maintains an extremely low operating potential (~100 mV) and continuous salt extraction with unlimited removal capacity. Comparison of the use of ferri-/ferrocyanide, pure ferricyanide and ferrocyanide solutions indicate that the ultra-low energy consumption can be ascribed to the excellent electrochemical properties of the ferri-/ferrocyanide couple and the extremely low overpotential of the redox reactions owing to the synergistic effect of sufficient simultaneous ferrocyanide oxidation and ferricyanide reduction in the flow electrolyte streams. Our research provides a route for ultra-low energy desalination based on voltage suppression via use of facile redox couple mediators.